The 1812 Aponte Rebellion in Cuba and the Struggle against Atlantic Slavery - Childs, Matt D., 1970- (Book collections on Project MUSE., 2006)
In 1812, a series of revolts known collectively as the Aponte Rebellion erupted across the island of Cuba, comprising one of the largest and most important slave insurrections in Caribbean history. This title provides an analysis of the rebellion, situating it in local, colonial, imperial, and Atlantic World contexts.